1998
DOI: 10.1111/j.1744-7348.1998.tb05836.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential benefits from cultivar specific red clover ‐potato crop rotations

Abstract: The aim of this study was to determine if endophytic bacteria could contribute to cultivar specific interactions between red clover (Trifolium pratense L.) and potatoes (Solanum tuberosum L.) in crop rotations. Endophytic bacteria were isolated from the roots of four red clover cultivars (AC Charlie, Altaswede, Marino and Tempus) grown in the field. Populations of bacteria from each cultivar were similar. The most abundant genus was Rhizobium, but species of Curtobacterium, Pseudomonas, and Xanthomonas were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Some earlier workers also investigated the effects of isolation media on species richness in twigs and leaves of Chamaecyparis thyoides. It was found that 1% malt extract and 2% yeast extract with 50 ppm each of Streptomycin and chlortetracycline gave the highest species richness for endophytic isolation [28]. One source of variation in the number of species could be the composition of the medium, as well as suitability of their constituents for fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier workers also investigated the effects of isolation media on species richness in twigs and leaves of Chamaecyparis thyoides. It was found that 1% malt extract and 2% yeast extract with 50 ppm each of Streptomycin and chlortetracycline gave the highest species richness for endophytic isolation [28]. One source of variation in the number of species could be the composition of the medium, as well as suitability of their constituents for fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Crop sequences can favour the build-up of beneficial endophytic bacterial populations (Peters et al 2003). For example, certain cultivars of red clover have been found to foster the development of rhizospheric and endophytic bacteria that promote the growth of subsequent potato crops (Sturz and Christie 1998). Lupwayi et al (2004) reported the distribution of R. leguminosarum bv.…”
mentioning
confidence: 99%
“…As mutualists, endophytes have been shown to elicit functional consequences on their plant host (Schardl et al ., ), in terms of improved water and nutrient uptake (Pillay & Nowak, ), nitrogen fixation (Krause, ), assisting with herbivore resistance by producing toxic secondary metabolites (Siciliano, ), improving the capacity to resist disease (Choudhary & Johri, ) and by promoting plant growth and overall primary productivity (Compant et al ., ). In addition, plant‐endophyte associations have been found to confer partial tolerance to environmental toxins such as heavy metals and chemicals (Barac, ; Ma, ; Sturz & Christie, ). Bacterial endophytes have been isolated and identified from tubers (Sessitsch et al ., ), stems, fruit, and seeds (Olivares et al ., ).…”
Section: Introductionmentioning
confidence: 99%